Case Report: a novel missense variant of FGD5 in a family with tetralogy of Fallot - Liu, Meng-Wei; Dong, Yi; Xiang, Rong; Wu, Liping (Frontiers in Genetics, 2025)
BackgroundCongenital heart disease (CHD) is among the most prevalent birth defects in newborns, with tetralogy of Fallot (TOF) being a classic example. Within weeks to months after birth, infants with TOF often exhibit cyanosis of the skin, lips, or nails and respiratory distress. Early medical intervention is crucial to enhance outcomes and ensure a better long-term prognosis.Methods and resultsA young Chinese couple was referred for prenatal counseling at a gestational age of 26+3 weeks for fetal complex CHD, including pulmonary artery stenosis, a widened aorta with overriding, and absence of the ductus arteriosus in their affected fetus, who was later diagnosed with TOF. To determine the genetic basis of the congenital heart defect, whole-exome sequencing and Sanger sequencing were performed to identify potential pathogenic variants. Subsequently, a heterozygous missense variant (c. 3233C>A, p.T1078K) of FGD5 was identified in both the affected fetus and its unaffected carrier mother, demonstrating an inheritance pattern with irregular dominance. This variant is exceptionally rare in public genomic databases and determined to be the genetic cause of TOF in the proband.ConclusionWe identified a novel heterozygous missense variant of FGD5 in a Chinese family with TOF, which expands the genetic spectrum of the disease.